COMORBIDITIES IN PATIENTS WITH RHEUMATOID ARTHRITIS - Болтаева Майрам Миралиевна (Web of Journals Publishing, 2025)
The analysis of the clinical, morphological and immunological significance of small intestine pathology in rheumatoid arthritis (RA) was carried out. The study included 120 patients with RA. The patients were assigned according to the DAS index 28. All received basic anti-inflammatory therapy. Symptoms of intestinal dysfunction, the presence of dysbiotic disorders, neuroendocrine imbalance were taken into account, endoscopic and morphological features of colonobies in patients with RA were studied. RA is associated with functional and structural changes in the intestinal mucosa. Pronounced disorders of the intestinal microecology are recorded with a high degree of RA activity. Intestinal dysfunction in RA with a DAS index of 28 > 5.1 is associated with significant changes in mast cells and apudocytes producing substance P and vasointestinal peptide.
Keywords: Rheumatoid arthritis, intestine, dysbacteriosis, diffuse endocrine system (DES).